Spatial Modeling of Flood-Vulnerability as Basic Data for Flood Mitigation - Iin Arianti; Muhammad Rafani; Nurul Fitriani; . Nizar (Salehan Institute of Higher Education, 2023)
Identifying risks in flood-prone areas is necessary to support risk management decisions. This research was conducted to establish a vulnerability model of flood hazards in the city of Pontianak. The model was based on the scoring and weighting of biophysical factors. The AHP method and logical formulations were used to establish the model. The result showed that the accuracy of the model used by AHP to determine the vulnerability of floods was 80% in Pontianak City. The accuracy of the model using logical formulations to determine the vulnerability level of a flood was 84%. The Kappa accuracy value in model 1 is 76.7%. The model of flood vulnerability explains that most of Pontianak City has a very high level of flood vulnerability, which is 31,440,568.8 m2 or 29.11% of the total research area of 108,003,319.8 m2. The vulnerable area is 29,945,485.7 m2 or 27.73%, and the less safe area is 22,126,936.3 m2 or 20.49%, with the safe area being 24,490,328.7 m2or 22.67% of the total area. This research contributes to the government to establish policies regarding flood management and urban development in the future, and as an effort to mitigate against flooding. Doi: 10.28991/CEJ-2023-09-04-02 Full Text: PDF